2010
DOI: 10.1021/jp1039892
|View full text |Cite
|
Sign up to set email alerts
|

Interface Structures of La0.67Sr0.33MnO3/SrTiO3 Superlattices Studied by TEM and EELS

Abstract: The layered structures of La 0.67 Sr 0.33 MnO 3 /SrTiO 3 superlattices have been investigated by energy filtered transmission electron microscopy (EFTEM) and spatially resolved electron energy loss spectroscopy (EELS). A general picture of the elemental distribution of the chemically modulated layers was given by the EFTEM images. Chemical shift in both Ti-L 2,3 and Mn-L 2,3 edges, together with an appearance of distinctive shoulders in both Mn-L 3 and Mn-L 2 edges at the interfacial region were observed. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…3a and b are taken from the LSMO layer and the lower ones are taken from the LSMO/STO interface. The similar trends of peak shifting are observed for both Mn-L 2,3 and Ti-L 2,3 edges when the electron probes move from the LSMO layer to the LSMO/STO interface: the energy positions of Mn-L 2,3 and Ti-L 2,3 edges shifted towards lower-energy losses (red-shifted), suggesting a local understoichiometry of oxygen around Mn and Ti at the interfacial region [11]. The large lattice mismatch and non-stoichiometry in the near-interface region all contribute to the formation of TDs.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…3a and b are taken from the LSMO layer and the lower ones are taken from the LSMO/STO interface. The similar trends of peak shifting are observed for both Mn-L 2,3 and Ti-L 2,3 edges when the electron probes move from the LSMO layer to the LSMO/STO interface: the energy positions of Mn-L 2,3 and Ti-L 2,3 edges shifted towards lower-energy losses (red-shifted), suggesting a local understoichiometry of oxygen around Mn and Ti at the interfacial region [11]. The large lattice mismatch and non-stoichiometry in the near-interface region all contribute to the formation of TDs.…”
Section: Resultssupporting
confidence: 67%
“…In our previous studies, we have observed oscillatory exchange coupling and enhanced magnetoresistance in such superlattices [9, 10]. The study on the electronic structures evolution across the interface of the superlattice provides a plausible explanation for the observed physical properties, that is, a stronger crystal field and/or a partial loss of oxygen at the interfacial regions [11]. In this reported work, we looked at different aspect of the LSMO/STO superlattices, studied the defects nature and the evolution of defects across multiple interfaces, by analysing details of the cross‐sectional bright field TEM micrograph.…”
Section: Introductionmentioning
confidence: 99%
“…The non-splitting Ti-L 3 /L 2 edge suggests the octahedral coordination of titanium atoms with oxygen. [23][24][25] The O-K edge shows a single peak, conrming the unoccupied oxygen p state. 26 The Raman spectrum analyses also conrm the presence of anatase TiO 2 and some graphitic carbon in the obtained materials (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we focus on the tetragonal BFO and apply it to the multifunctional devices. Spintronic devices are studied intensively in various fields, such as the organometallic spin filter, molecular spin-valve devices, and oxide spintronics. , Half-metallic materials are crucial to the spintronic devices, owing to the 100% spin polarization. , LSMO with a high ferromagnetic Curie temperature of 370 K is a prototypical ferromagnetic half-metallic material, which shows a magnetoelectric effect via accompanying with various ferroelectric materials, like BaTiO 3 , Pb­(Zr 0.52 Ti 0.48 )­O 3 , and rhombohedral BFO. , …”
mentioning
confidence: 99%